Tests and design of short steel tubes filled with rubberised concrete. (1st April 2016) - Duarte, A.P.C.; Silva, B.A.; Silvestre, N.; de Brito, J.; Júlio, E.; Castro, J.M.
Graphical abstract: Highlights: Strength and ductility of short steel tubes infilled with rubberised concrete (RuCFST) are studied. RuCFST columns exhibit lower stiffness and strength than CFST columns, but also higher ductility. Ductility increases 40–150% as one goes from NC to RuC (0–15% of rubber particles). This ductility increase depends on the cross-section shape, being most effective for circular sections. This evidence benefits structures in seismic areas, where energy dissipation requirements are mandatory. Abstract: An experimental investigation on the strength and ductility of short steel tubes filled with rubberised concrete (RuC), sourced from recycled scrap tyres, is presented in this paper. Firstly, a brief literature review on (i) concrete-filled steel tubes (CFST) and (ii) mechanical characterisation of rubberised concrete is presented. Then, the experimental investigation is described and test results are shown and discussed, namely, the assessment of (i) RuC and steel mechanical properties and (ii) RuCFST column structural properties. The influence of various parameters, such as the cross-section shape (square, rectangular, circular), steel grade, and concrete mix (standard concrete versus RuC), on the short column strength and ductility is analysed and discussed. Eurocode 4 is considered (i) to determine the strength of the tested columns and, in particular, (ii) to assess its applicability to RuCFST columns based on a comparison with the experimental results. The main conclusion of this research is that RuCFST short columns present higher ductility than those made of standard concrete, even though they also show lower strength. This improved ductility is noticeable in columns with circular sections, rather than in square and rectangular sections. From a practical viewpoint, this could be a major benefit for structures in seismic areas where energy dissipation is needed.